Signaling of High Mobility Group Box 1 (HMGB1) through Toll-like Receptor 4 in Macrophages Requires CD14 - Sodam Kim; Sun Young Kim; John P. Pribis; Michael Lotze; Kevin P. Mollen; Richard Shapiro; Patricia Loughran; Melanie J. Scott; Timothy R. Billiar (BMC, 2013)
Abstract High mobility group box 1 (HMGB1) is a DNA-binding protein that possesses cytokinelike, proinflammatory properties when released extracellularly in the C23-C45 disulfide form. HMGB1 also plays a key role as a mediator of acute and chronic inflammation in models of sterile injury. Although HMGB1 interacts with multiple pattern recognition receptors (PRRs), many of its effects in injury models occur through an interaction with toll-like receptor 4 (TLR4). HMGB1 interacts directly with the TLR4/myeloid differentiation protein 2 (MD2) complex, although the nature of this interaction remains unclear. We demonstrate that optimal HMGB1-dependent TLR4 activation in vitro requires the coreceptor CD14. TLR4 and MD2 are recruited into CD14-containing lipid rafts of RAW264.7 macrophages after stimulation with HMGB1, and TLR4 interacts closely with the lipid raft protein GM1. Furthermore, we show that HMGB1 stimulates tumor necrosis factor (TNF)-α release in WT but not in TLR4−/−, CD14−/−, TIR domain-containing adapter-inducing interferon-β (TRIF)−/− or myeloid differentiation primary response protein 88 (MyD88)−/− macrophages. HMGB1 induces the release of monocyte chemotactic protein 1 (MCP-1), interferon gamma-induced protein 10 (IP-10) and macrophage inflammatory protein 1α (MIP-1α) in a TLR4- and CD14-dependent manner. Thus, efficient recognition of HMGB1 by the TLR4/MD2 complex requires CD14.